Pengaruh E-Service Quality Terhadap Loyalitas Pengguna Aplikasi MyTelkomsel - Ibrahim, Ali; Elisa, Felia Sonya; Fernando, Jose; Salsabila, Lulu; Anggraini, Nadya; Arafah, Siti Nur (Forum Kerjasama Pendidikan Tinggi, 2021)
MyTelkomsel is a service in the form of an application that can be accessed by mobile which was launched by Telkomsel to make it easier for its customers, where the application is in the form of self service for its users. However, the MyTelkomsel application still gets several complaints from its users, such complaints as failure in the login process, failure in the process of making payments/transactions, the types of packages offered on each user's device are different and sometimes do not match the customer's budget, as well as some comments from users. regarding customer service that makes them dissatisfied. The purpose of this research is to determine whether there is an effect of e-service quality on user loyalty in the MyTelkomsel application. In this research, the model used is E-Service Quality. Methods of collecting data in this research, using online questionnaires to MyTelkomsel user respondents through the assistance of social media for the dissemination process. The sample used in this research was 50 respondents from MyTelkomsel application users. The type of sampling technique used in this research is random sampling. For the data analysis process from this research using the SmartPLS and SPSS applications. The results of the research indicate that e-service quality has a significant influence on customer loyalty in the MyTelkomsel application